Advances in Speech-language Pathology - Dreux Fernandes, Fernanda M. (IntechOpen, 2017)
Speech-language pathology has different practice and research histories, standards, methods, and challenges in different countries and regions. Awareness of these different realities may contribute to the scientific development of the field and improve the services delivered to different populations. Sharing solutions to similar problems in different contexts can increase evidence-based practice that is relevant in specific situations. The aim of this book was to build a panel of contributions from different countries and several areas of research. Authors were invited to contribute with their newest conclusions and results about the themes they considered most relevant. The result includes discussions about new theoretical trends, research results, and new proposals for assessment and intervention.